Application of Social Cognitive Theory on Factors Related to Alcohol Consumption in Adolescents: Meta-Analysis - Hana Fathiya Dasairy; Argyo Demartoto; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Alcoholic drinks are all types of drinks that contain ethanol. In several countries, alcohol is a drink that is easy to obtain, so it tends to be abused a lot. Continuous alcohol consumption can lead to alcohol dependence. The purpose of this research is to analyze the application of social cognitive theory about the factors that influence alcohol consumption in adolescents. Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: Teenagers. Intervention: anxiety, drinking parents and drinking friends. Comparison: No anxiety, no drinking parents, and no drinking friends. Outcome: Consumption of alcoholic beverages. The online databases used are: PubMed, Google Scholar, Science Direct, and Scopus with the keywords “factors associated” AND “alcohol consumption” AND “anxiety” OR “parents alcohol consumption” OR “peers alcohol consumption” AND “adolescents” AND